Editorial - González-Campo, Carlos Hernán (Cuadernos de Administración, 2020)
The globalization of information, even more so at times like these, has placed scientific journals into very competitive contexts of news or articles, which circulate and become publicized even faster, for example, social networks. This makes it necessary for scientific journals to increasingly use technological elements and resources to gain greater visibility and disseminate the knowledge authors shared for their readers. To such an end, authors need to be absolutely clear about the importance of metadata, correct citation, or rigorous referencing in standardized formats, because in some way, in addition to good content and consistent structure, depending on the type of paper, these bring on broader readership, downloads, and citations for their papers. In addition to addressing these technical elements, journals must have their editorial processes under constant transformation as determined by self-evaluation processes coupled with strategies that seek improvement. Another vital element is to define the journal’s scope and approach because these elements help both authors and readers to decide whether it is the right journal to publish or consult. In Cuadernos de Administración, the editorial and production evaluation process is understood as a peer dialogue in an academic context, and opinions, recommendations, and editorial decisions are framed in respect among the process participants from each one’s role. It is the academic community that develops around a scientific journal that determines its future and relevance. Issue 67 of the journal Cuadernos de Administración, May-August 2020, after a double-blind evaluation and the editorial process, set out to publish ten papers on scientific and technological research and one review paper. The first group contains scientific and technological research papers. The group’s first one is entitled “Organizational characterization of craftsmanship in northern of Valle del Cauca.” Therein, the authors present the organizational state of artisans in developing their profession or trade in the municipalities that make up the northern region of Valle del Cauca (Colombia). Using a documentary analysis and in consultation with stakeholders, they identified the territory’s comparative and competitive advantages from the productive vocation and its relationship to artisanal production. The results seek to propose innovative strategies to strengthen the region’s craftsmanship. The second article, presents the results of a research that sought to establish the effectiveness of the constructivist training method in the business administration program, based on the Balanced Scorecard and others management tools, and from the students’, the entrepreneurs’, the institutions’ and the teaching perspectives. The study employed the quantitative and qualitative analysis coupled with surveys applied to a group of students and entrepreneurs. The authors hope these results will contribute to improving teaching in these programs. The third paper, “Sustainable design of reverse supply chain for solid waste in Mexico,” proposes an Inverse Supply Chain procedure for Urban Solid Waste in the Mexican municipality of Netzahualcóyotl. The fourth paper presents the results of surveillance, and strategic intelligence applied on the scientific, technological, and commercial trends of 10 natural ingredients prioritized in the project “Strengthening R&D capabilities for the production of natural ingredients (NI) from residual biomass in Palmira, Vall del Cauca.” The findings analyze pineapple, soursop, and peach palm fruit. The fifth manuscript, “Identification of organizational leaders’ managerial competences in the passiflowers producing sector in the department of Huila,” results from a research that sought to identify managerial competencies in the sector. The authors used mixed methods to enable managers of passiflower producing associations in the production chain to obtain a map of managerial competencies to strengthen their managerial capabilities and competitiveness. In the sixth article, the authors aim to establish the factors that influence mobile banking’s embracing by microentrepreneurs from the Theory of Planned Behavior (PB) and the TPB extended to relative advantage and perceived risk. To that end, they used quantitative methods on a sample of 101 microentrepreneurs. The findings confirm the effect of attitude, subjective norms, behavior control, and relative advantage over mobile banking adoption. The seventh paper, “Effects of the prices of mining and energy commodities on the Colombian economy,” evaluates the impact from price changes shocks in mining and energy goods that bear the highest weight on Colombian exports, i.e., oil, coal, and nickel. In this vein, they observe the different effects on economic aggregates. A database consisting of 129 variables for the 2001-2016 period was used, and a FAVAR model was estimated. The eighth article, analyzes the impact of organizational strategies on the financial performance of large-, medium- and small-sized rubber and plastic companies in the Metropolitan Area of Bucaramanga, Colombia. The authors used qualitative and quantitative methods. They analyze indicators and then characterize the strategic orientation and performance in 2017 through a survey. The ninth paper, “Adjustment by the effect of size on the cost of equity: Pending practice in the capital budget in Colombia,” identifies and analyzes the implications of capital budget techniques implemented by large-, medium- and small-size companies in connection to the use and calculation of the discount rate. For this purpose, they use descriptive analysis to characterize a group of 182 Colombian companies. The tenth article, entitled “Training for professional judgment in accounting education,” aims to analyze, in the educational projects of high-quality Public Accounting programs in Colombia, the approach to professional judgment and critical thinking as a factor contributing to the formation of this judgment in accountants. They use a qualitative-documentary methodology on the Syllabus of accredited universities’ programs. The last paper, “Gender job gaps and challenges in the digital economy: Findings from global governance entities,” makes a descriptive review of the most recent studies on gender labor gaps as prepared by the leading entities of global governance, focusing on technological and scientific areas. Moreover, the author shows the risk of erosion, and even loss, of women’s progress in recognition, inclusion, and equality. The author also argues that despite the achievements in closing educational, health, and economic gaps, the wage gap and the access-to-management gap continue to exist. We hope that the eleven papers in this issue will contribute knowledge to the sciences of administration. The content of each paper is its authors’ responsibility and not the journal’s. We hope that they will contribute to future reflections and research. We thank the authors, reviewers, committee members, and readers of our journal for being part of this academic community.